2006
DOI: 10.1021/ic061604s
|View full text |Cite
|
Sign up to set email alerts
|

[Me4N](NiII(BEAAM)):  A Synthetic Model for Nickel Superoxide Dismutase That Contains Ni in a Mixed Amine/Amide Coordination Environment

Abstract: Nickel superoxide dismutase (NiSOD) is a metalloenzyme that converts O2*- into H2O2 and O2 by cycling between Ni(II) and Ni(III) oxidation states. Reduced NiSOD contains Ni(II) in a square-planar N2S2 coordination environment formed by two cysteinate S atoms, an amide N, and an amine N to Ni(II). [Me4N](Ni(II)(BEAAM)) represents the first NiN2S2 complex containing Ni in a mixed amine/amide environment. [Me4](Ni(II)(BEAAM)) contains Ni-S bonds at 2.177(2) and 2.137(2) A and Ni-N bonds at 1.989(7) and 1.858(6) A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
75
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 18 publications
9
75
0
Order By: Relevance
“…12,21,34,40,42,54−56 The Grapperhaus research group and our research group have suggested this is due (in part) to the electronic consequences of the mixed amine/amidate ligand set. 21,40,42,54 Harrop and Grapperhaus have also suggested that hydrogen bonds to the cysteinate sulfurs will protect the cysteinates from oxidative damage induced by ROSs. 34,54 This study shows that {Ni II (SOD m1 )} contains both a Ni II -S(H + )-Cys(6) moiety and water cysteinate hydrogen bonds, which likely enhance its observed robustness against oxidative damage in addition to the electronic finetuning of the Ni−S bond imparted by the primary coordination environment.…”
Section: ■ Discussionmentioning
confidence: 99%
“…12,21,34,40,42,54−56 The Grapperhaus research group and our research group have suggested this is due (in part) to the electronic consequences of the mixed amine/amidate ligand set. 21,40,42,54 Harrop and Grapperhaus have also suggested that hydrogen bonds to the cysteinate sulfurs will protect the cysteinates from oxidative damage induced by ROSs. 34,54 This study shows that {Ni II (SOD m1 )} contains both a Ni II -S(H + )-Cys(6) moiety and water cysteinate hydrogen bonds, which likely enhance its observed robustness against oxidative damage in addition to the electronic finetuning of the Ni−S bond imparted by the primary coordination environment.…”
Section: ■ Discussionmentioning
confidence: 99%
“…[20] It has been argued that the mixed amine/amide coordination at the active site of NiSOD plays a crucial role in tuning the redox chemistry and reactivity of the active site. [13,14] Thus, filled-filled interactions between the p-donating amide ligand and the Ni-p orbitals destabilize metal-based orbitals, thereby facilitating electron transfer from Ni II to O 2 C À to generate a Ni III center, rather than Sbased radicals, in the catalytic cycle.…”
Section: N]a C H T U N G T R E N N U N G [Ni Ii a C H T U N G T R E Nmentioning
confidence: 99%
“…[20] The addition of pyridine to solutions of 1 at 293 and 253 K does not change the profile of the UV/Vis spectrum of 1, suggesting that pyridine does not bind to 1 over this temperature range. The oxidation of 1 and 2 to 1 + and 2 + , respectively, was monitored spectroelectrochemically using an optically transparent electrode cell (Figure 8).…”
mentioning
confidence: 94%
“…[11,20,21] The UV region in Figure 2 shows only one broad band centered around 38 167 cm À1 (262 nm; e = 10 787 m À1 cm…”
mentioning
confidence: 99%